Utopian Visions and Real Estate Dreams: The Eco‐city Past, Present and Future. Issue 2 (February 2014) - Rapoport, Elizabeth
Abstract This article traces the evolution of the eco‐city as a concept and an urban planning model over the last 40 years, outlining the various definitions, applications and critiques of the term historically and today. What distinguishes the eco‐city from work on sustainable urbanism more broadly, the article argues, is its attempt to create a comprehensive and transferable model of sustainable urban development. Over the years, the eco‐city, in both theory and application, has evolved along with broader trends in environmental thought. The idea of the eco‐city originally emerged out of counterculture movements of the 1960s and 1970s as an approach to urban development that would respect environmental limits. Contemporary eco‐city projects attempt to transcend these limits and are often driven as much by economic objectives as environmental ones. Although many eco‐city projects market themselves as models for future urban development, the article argues that they are better seen as sites of experimentation and innovation, helping drive broader socio‐technical transitions. The article concludes that the ability of eco‐cities to achieve their utopian ambitions may be limited by the realities of operating within a profit‐driven, entrepreneurial planning environment. However, they can still play a valuable role, providing a place to test new ideas and an ideal to aspire to.